Estimation of population variance using kernel matrix. Issue 3 (3rd April 2019) - Hanif, Muhammad; Shahzad, Usman
Abstract: This study considers the issue of estimating the population variance utilizing trace of kernel matrix in absence of non-response under simple random sampling scheme. Further, Mohanty and Sahoo (1995) transformation is applied on supplementary variable. Some enhanced families of estimators have been proposed along with their biases and mean square errors. Efficiency comparisons of the proposed families of estimators with the reviewed ones using single auxiliary variable have been made. Finally, an empirical illustration is carried out to assess the performance of the proposed families over existing ones.